2011
DOI: 10.1111/j.1550-7408.2011.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and Ultrastructural Description of Meglitschia mylei n. sp. (Myxozoa) from Myleus rubripinnis (Teleostei: Serrasalmidae) in the Amazon River System

Abstract: Meglitschia mylei n. sp. found in the gall bladder of the teleostean fish Myleus rubripinnis (Serrasalmidae) from the middle Amazonian region of Brazil is described using light and transmission electron microscopy. The spores observed in the bile averaged 24.6±0.8 μm long, 8.7±0.4 μm wide and 5.1±0.3 μm thick and were strongly furcate and arcuate ∩-shaped composed of two symmetric equal-sized valves, up to ∼70 nm thick. Each valve possessed one opposed tapering appendage, 20.1±0.7 μm long, oriented parallel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…The morphological and ultrastructural aspects of the myxospores showing a furcate and arcuate ∩-shaped organization show that these myxospores are similar with those previously described belonging to the genus Meglitschia [1][2][3][4]. Based on the arc shape of the myxospore with two tapering caudal appendages oriented to the basis of spores, on the number and position of the PC and of the polar filament coils (PFc) and arrangements, the morphology of the myxospores suggested that this parasite belongs to genus Meglitschia.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The morphological and ultrastructural aspects of the myxospores showing a furcate and arcuate ∩-shaped organization show that these myxospores are similar with those previously described belonging to the genus Meglitschia [1][2][3][4]. Based on the arc shape of the myxospore with two tapering caudal appendages oriented to the basis of spores, on the number and position of the PC and of the polar filament coils (PFc) and arrangements, the morphology of the myxospores suggested that this parasite belongs to genus Meglitschia.…”
Section: Discussionmentioning
confidence: 64%
“…The observation in aquarium of the living fish does not present altered behavior. The typical morphology of the myxospores suggests that the present microparasite belongs to the genus Meglitschia, according the previous descriptions [1][2][3][4].…”
Section: Case Descriptionmentioning
confidence: 81%
See 3 more Smart Citations